A5.06 Ultrasound-defined tenosynovitis predicts ra in patients with recent-onset inflammatory arthritis. (24th February 2016) - Sahbudin, I; Pickup, L; Nightingale, P; Allen, G; Cader, Z; de Pablo, P; Buckley, CD; Raza, K; Filer, A
Abstract : Background and objective: Tenosynovitis is common in early arthritis and the OMERACT Ultrasound Task Force recommended that US is a reproducible tool for evaluating tenosynovitis (TS) in RA. However, the value of US-defined tenosynovitis (TS) in the prediction of RA development is unclear. We assessed the ability of US-defined TS to predict the development of persistent RA in a prospective cohort of patients with early arthritis. Methods: 107 patients with clinically apparent synovitis of at least one joint and symptom duration ≤3 months underwent baseline clinical, laboratory and tendon US assessments and the presence of grey scale and Power Doppler TS at 16 bilateral tendon compartments was determined [bilateral fingers (flexor compartments), wrists (extensor and flexor compartments), shoulders (biceps tendon), ankles (anterior extensors, peroneals, posterior tibialis)]. Outcome was determined after 18 months, applying the 2010 ACR/EULAR classification criteria for RA. The predictive values of US-defined TS for persistent RA were compared with clinical and serological variables. Results: A total of 3424 tendon compartments were included in the analysis. 43 patients developed persistent RA (RA), 20 patients developed non-RA persistent disease (NRAP) and 44 patients had resolving disease at follow-up. All groups had evidence of TS in at least one tendon compartment at baseline (RA 85%, NRAP 71%, and Resolving 71%). In multivariate logistic regression, extensor carpi ulnaris (ECU) and digit flexor tendon involvement were predictive of persistent RA and provided additional predictive data over and above the presence of high levels of autoantibodies and clinical involvement of more than 10 joints [ECU or digit flexor TS (OR = 5.25, p = 0.001), >10 clinically tender or swollen joints (OR = 7.96, p < 0.001), RF or ACPA high-positivity (OR = 7.31, p = 0.001); AUC = 0.86, Nagelkerke's R 2 = 0.499]. Conclusion: This is the first study to illustrate that US-detected TS is predictive of persistent RA in patients with early arthritis. ECU and digit flexor tendon scanning provides optimal predictive data over and above clinical and serological variables.